How Does Ceramic-Based Scaffold Microarchitecture Impact Maxillofacial Bone Regeneration? A Systematic Review of Large Animal Models - Ana M. P. Baggio; Yannick M. Sillmann; Pascal Eber; Felicia R. S. Michallek; Joao L. G. C. Monteiro; Ana P. F. Bassi; Fernando P. S. Guastaldi (Applied Sciences, 2025)
Critical-sized bone defects (CSBDs) are injuries that exceed the body’s natural capacity for repair and require external intervention. These defects are particularly challenging in the mandible, often resulting from trauma, tumor resection, or implant-related complications. Effective treatment involves scaffold designs that support vascularization, bone formation, and sufficient mechanical strength. This systematic review aims to assess whether ceramic-based scaffold properties, including porosity, pore size, and macroscopic characteristics, improve vascularization, bone formation, and the mechanical properties in the treatment of CSBDs in large animal models. A search of databases (PubMed, Embase, and Web of Science) identified 11 in vivo studies involving CSBDs (>2 cm), ceramic scaffolds, and histological analysis. Findings indicate that scaffolds with porosity exceeding 50% yield optimal outcomes by striking a balance between cell infiltration and mechanical stability. Pore sizes ranging from 300 μm to 700 μm are ideal for vascularization and bone ingrowth. Three-dimensional (3D) printing shows promise in creating scaffolds with precise and reproducible features. However, the studies varied significantly in their methodologies and outcomes, with no consensus on the optimal scaffold properties for mandibular CSBDs. Scaffold porosity and pore size play key roles in promoting vascularization and bone regeneration. Various animal models reinforce this finding, suggesting that scaffold architecture is crucial for biological integration and functional outcomes. This review highlights the importance of standardized research protocols and clear design criteria in enhancing the success of bone regeneration. Future research should investigate emerging biomaterials and new scaffold technologies to overcome current limitations in clinical applications.